Application of Project Based Learning Model for Class V Students Theme 5 Sub Theme 1 Ecosystem Materia - Purwanti, Peni; Safitri, Aguslia; Pusporini, Henny; Kusumaningrum, Shirly Rizki; Dewi, Radeni Sukma Indra (Jurnal Ilmiah Mandala Education (JIME), 2022)
The purpose of this study is to describe learning outcomesstudentcognitivelythrough a project-based learning model for class V students on ecosystemmaterial. The type of research conducted in this research is class actionresearch (CAR), In CAR which ingeneral there are four stages that arecommonly passed, namely (1) planning, (2) implementation, (3) observation,and (4) reflection.Data collection techniques in this research consist of:observation, documentation, and tests. The subjects in this study were fifthgrade students at UPT SDN Pasirharjo 1 Blitar. The research subjects were 23students consisting of 9 male students and 14 female students. The type ofdata that will be collected in this study is data on science learning outcomesfor fifth gradestudents of UPT SD Negeri Pasirharjo 1 Blitar. The results isshowed that students' learning outcomes were cognitively improved. Theimplementation of science learning on ecosystem materials by applying thePjBL model in cycle I and cycle II were 78.48 with good criteria and 81.95with very good criteria.